The role of Vitamin D3 in ocular fibrosis and its therapeutic potential for the glaucomatous trabecular meshwork - Morelli-Batters, Alexander; Lamont, Hannah C.; Elghobashy, Mirna; Masood, Imran; Hill, Lisa J. (Frontiers in Ophthalmology, 2022)
Glaucoma is the leading cause of irreversible blindness globally. The most prevalent subtype, Primary Open Angle Glaucoma (POAG), is characterized by increased intraocular pressure (IOP), damage to the optic nerve head and irreversible visual loss. IOP increases aqueous humour (AqH) outflow is reduced through the trabecular meshwork (TM) and Schlemm’s canal (SC). Increased outflow resistance is partly due to TM/SC dysregulation, including loss of normal trabecular meshwork cell (TMC) function, following increased levels of oxidative stress within TMC, dysregulated extracellular matrix (ECM) deposition and remodeling alongside alterations in TMC phenotype and apoptosis. Current widely available POAG treatments do not target the aberrant expression of ECM in the TM directly. As a result, most drug treatments can fail as the underlying pathological process continues unabated. Rho-kinase inhibitors have demonstrated the benefit of restoring TM/SC function, however there is a clear need to develop further treatment strategies that can target the underlying cellular processes which become dysregulated within the TMC during POAG pathogenesis. Vitamin D is suggested to be beneficial in alleviating the symptoms of fibrosis and inflammation in soft tissues. It has important functions in many major organ systems, including regulation of calcium, phosphate and parathyroid hormone. Evidence suggests that Vitamin D3 modulates ECM turnover through the conventional TGFβ-SMAD signaling, which is associated with the development of POAG. The link between Vitamin D3, inflammation and fibrosis within ocular tissues will be discussed and the potential roles of Vitamin D3 in the management of POAG patients will be explored within this review.